Processamento da co-referência: pronomes lexicais, nomes repetidos, hiperônimos e hipônimos coino formas de retomada anaforica inter-sentencial do sujeito em português brasileiro - Queiroz, Karla Lima de (2009)
The co-reference is usually defined as a strategy of textual progression that recalls a previous entity, called antecedent, through the use of an anaphora. Different areas of science have studied the co-reference for its relevance to the local coherence, as well as to the discourse comprehension. However, a crucial question remains and requires to be clarified, that is about the cognitive mechanisms and the linguistics principles that underlie the choice of anaphora among the various forms of the language. The current work has its theoretical connection with Experimental Psycholinguistics which deals with the process of the phases, and more especifically with the processing of the co-reference. This work compares the efficiency of the lexical pronouns vs. repeated-name, as well as hiperonimos vs. hiponimos, both seen as ways of one's inter-sentential anaphoric recalling in Brazilian Portuguese. It was also verified that the wide range of the Centering Theory (Grosz, Joshi e Weinstein, 1983, 1995), which states a slower effect known as Repeated NP Penalty when recalling an antecedent using the repeated noun instead of a pronoun, as well as the The Informational Load Hypotheses (Almor 1990, 1999, 2000), as an alternative concept that connects the processing cost with the discourse function. For that, the current research used three on-line self paced reading experiments and analyzed its results by using both the T-Test and the ANOVA one. In the first experiment the lexical pronouns were read faster than the repeated pronouns, in accordance to the Centering Theory and the he Informational Load Hypotheses. The second experiment, the co-reference was better established by the hiperônimos instead of hipônimos, reinforcing the cost-funcion principle stated by Almor (1990, 1999, 2000), while the Repeated NP Penalty by Gordon et. al. (1993, 1995), is concerned about the dichotomy between lexical pronouns vs repeated nouns. The syntactic prominence was also discussed in Chamber's & Smith (1999) research as well as in Leitão's (2005), but the third experiment stated the independent act of the syntactic prominence in relation to the type of the anaphora, even though that does not exclude the influence of the structural parallelism.